Ethno-environmental knowledge as a tool to combat indoor air pollution in low income countries: a case study from rural communities in Pakistan - Nasir, Zaheer A.; Colbeck, Ian; Bharucha, Zareen P.; Cintra Campos, Luiza; Ali, Zulfiqar (Cranfield University, 2014)
It has recently been estimated that 4 million deaths each year are associated with air pollution originating from household solid fuel use. Interventions to reduce biomass fuel-related emissions can yield a diverse stream of benefits including improved public health, socio-economic development, reduced land degradation and climate change mitigation. This study investigates the use of indigenous knowledge to inform interventions to combat indoor air pollution at a rural site in the Punjab province of Pakistan. The results indicate that the majority of people using biomass fuel had knowledge of its ill health effects. A range of methods were utilised to reduce indoor smoke including cooking in open spaces, use of chimneys, better ventilation and use of dry fuel. Education and housing type showed a statistically significant relationship with awareness of methods to reduce indoor exposure to biomass smoke. These findings lend support to the notion that communities have indigenous knowledge and their own methods to reduce exposure to indoor smoke from biomass fuels; this knowledge can be used as tool to design and implement sustainable intervention strategies to reduce the risk of exposure to indoor air pollution. It is recommended that a community based intervention focusing on locally manufactured improved stoves and better designed cooking spaces would be a suitable intervention in this region.
Keywords: Indoor Air Pollution; Indigenous Knowledge; Interventions